Edaravone and cyclosporine A as neuroprotective agents for acute ischemic stroke. Issue 3 (17th May 2018) - Matsumoto, Shohei; Murozono, Michihiro; Kanazawa, Masahiro; Nara, Takeshi; Ozawa, Takuro; Watanabe, Yasuo
Abstract : It is well known that acute ischemic stroke (AIS) and subsequent reperfusion produce lethal levels of reactive oxygen species (ROS) in neuronal cells, which are generated in mitochondria. Mitochondrial ROS production is a self‐amplifying process, termed "ROS‐induced ROS release". Furthermore, the mitochondrial permeability transition pore (MPTP) is deeply involved in this process, and its opening could cause cell death. Edaravone, a free radical scavenger, is the only neuroprotective agent for AIS used in Japan. It captures and reduces excessive ROS, preventing brain damage. Cyclosporine A (CsA), an immunosuppressive agent, is a potential neuroprotective agent for AIS. It has been investigated that CsA prevents cellular death by suppressing MPTP opening. In this report, we will outline the actions of edaravone and CsA as neuroprotective agents in AIS, focusing on their relationship with ROS and MPTP. Abstract : Edaravone, a free radical scavenger, is the only neuroprotective agent for acute ischemic stroke (AIS) used in Japan. Cyclosporine A, an immunosuppressive agent, is a potential neuroprotective agent for AIS. In this report, we will outline the actions of edaravone and cyclosporine A as neuroprotective agents in AIS, focusing on their relationship with reactive oxygen species and the mitochondrial permeability transition pore.